Six rules for brand revitalization learn how companies like McDonald's can re-energize their brands - Light, Larry (Wharton School Pub., 2009)
This book teaches the invaluable lessons of one of the most successful brand revitalization projects in business history: the reinvigoration of McDonald's. Larry Light who spearheaded McDonald's breakthrough marketing initiatives, presents a systematic blueprint for resurrecting any brand, and driving it to unprecedented levels of success.
Includes bibliographical references and index. - Print version record
Keywords: McDonald's Corporation -- Case studies; Branding (Marketing) -- Management; Brand name products -- Management; Markenpolitik; Markenartikel; Management; Fallbeispiel; McDonald's Corporation; McDonald's Corporation; Case studies; Branding (Marketing); Management; Brand name products; Management; Product life cycle; Stratégie de marque; Gestion; Produits de marque; Gestion; Produits commerciaux; Cycle de vie; Schnellgastronomie; Markenführung; Strategisches Management; USA; Case studies